ANALISIS FINANCIAL STRESS INDICATOR SEBAGAI ALAT UKUR STABILITAS SEKTOR KEUANGAN INDONESIA - Difa Dini Asfari (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
Financial sector stability is difficult to define as there are many factors that influence it. Stress of the financial sub-sector can be used as a proxy to measure the stability of the financial sector. Financial stress index as a composite index which its components could be analyzed using factor analysis can be used as a tool to measure the financial sector stability. In this research I found that financial stress index, consisting of banking variable is the most relevant index for financial sector stability in Indonesia because the index is dominated by the banking component that is very sensitive to the volatility of macroeconomic conditions. In this study, the condition is represented by the rate of inflation and the BI rate.